Micro evidence on brazilian price stickiness and its consequences for sectoral real exchange rate and inflation persistence - Matos, Silvia Maria (2010)
The purpose of this thesis is to investigate the price-setting behavior in Brazil and, in particular, the effects on inflation and good-level real exchange rate persistence. This thesis is composed by three Chapters. In the first Chapter, we present the main stylized facts about the behavior of retail prices in Brazil using micro data from the CPI index computed by the Fundação Getulio Vargas. Moreover we construct time series of price-setting statistics and relate them to macroeconomic variables using regression analyses. In Chapter 2, we investigated the relevance of heterogeneity in countries price stickiness on good-level real exchange rate persistence, considering a newly constructed panel data set of relative prices of 115 common products between the U.S. and Brazil. Chapter 3 is devoted to the relation between sectoral price stickiness and inflation persistence.